The Health and Welfare of Rabbits as Indicated by Post-Mortem Findings at the Slaughterhouse - Valkova, Lenka; Vecerek, Vladimir; Voslarova, Eva; Zavrelova, Veronika; Conte, Francesca; Semerad, Zbynek (Animals, 2021)
The aim of the study was to assess post-mortem findings according to their localization and the nature of damage and to assess the standard of health and welfare of farmed rabbits on the basis of these findings. A total of 40,206 pathological findings were recorded in 1,876,929 rabbits slaughtered at slaughterhouses in the Czech Republic in the period from 2010 to 2019. Pathological findings on the limbs (0.84%), the trunk (0.71%), the kidneys (0.17%), and the liver (0.05%), along with generalized changes (0.37%), occurred most frequently. Findings of traumatic origin dominated among findings on the limbs and trunk, which indicates the inappropriate housing and handling rabbits on farms and during transport. Findings in the kidneys and liver were most often of a chronic nature having an evident correlation with the diet of intensively fed rabbits, with shortcomings in the diet having an impact on the parenchyma with chronic manifestations in the liver and kidneys. Among the generalized findings, multiple abscesses, which were probably associated with the infection of injuries occurring during fattening, and emaciation resulting from current husbandry practices, leading to insufficient feed intake or the development of disease in some individuals, predominated.
Keywords: rabbit; slaughter; welfare; veterinary inspection; health